Gender, politics, and society in Ukraine - Hankivsky, Olena; Salnykova, Anastasiya, 1983- (University of Toronto Press, 2012)
Gender, Politics, and Society in Ukraine is particularly innovative in its exploration of both women's and men's experiences and the ways in which gender relations shift over time in societies undergoing transitions to democracy.